Truth and metaphor - Shaiful Azrizal, Muhammad Alif Haikal; Abd Karim, Muhammad Hirzan Ifwad; Tuan Zainal Abidin, Tuan Muhammad Lukman; Md Romzi, Muhammad Aiman Hakimi; Saari, Muhammad Arfa (2024)
Slide Presentation: “Truth and metaphor”